Hubungan Perubahan Nilai Hematokrit dengan Tingkat Keparahan Demam Berdarah Dengue pada di RSUD Pandan Kabupaten Tapanuli Tengah Tahun 2024 - Martina Lailam Rambe; Samuel Joshua Hamonangan Tua Rajagukguk; Suandy Suandy (Publikasi Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus from the genus Flavivirus, which has four serotypes: DENV-1, DENV-2, DENV-3, and DENV-4. This virus can enter the human body through the Aedes aegypti and Aedes albopictus mosquitoes. The hematocrit value is a laboratory parameter needed to monitor the development of DHF. In DHF cases, there is an increase in hematocrit or hemoconcentration due to plasma leakage. Objective: To determine whether there is a relationship between changes in hematocrit values and the severity of dengue fever in children. Method: This study used an observational analytical study with a cross-sectional design. Result: The chi-square test yielded a p-value of 0.000, indicating a relationship between hematocrit and dengue fever severity in patients at Pandan Tapanuli Tengah Regional Hospital. Conclusion: This study found a significant relationship between hematocrit levels and dengue fever severity.